Soil-Transmitted Helminth Infections and Associated Risk Factors Among Primary Schoolchildren in the Koh Yao Islands of Southern Thailand - Nonthapan Phasuk; Prasit Na-Ek; Udomsak Narkkul; Stephen J. Scholand; Chuchard Punsawad (Journal of Tropical Medicine, 2025)
Soil-transmitted helminth (STH) infections are the most common parasitic infections worldwide, particularly in tropical regions. There are currently no reports on the prevalence of STH infections among children in Koh Yao District of Phang Nga Province, Thailand. Therefore, this study aims to assess the prevalence of STH infections and associated risk factors among primary schoolchildren. A school-based cross-sectional study was conducted among 243 schoolchildren aged 7 to 12 years from 12 rural primary schools across three subdistricts. Demographic data and associated risk factors were collected and analyzed. Stool samples were collected and examined for parasites using the formalin-ethyl acetate sedimentation concentration and the modified Kato-Katz methods. A multivariate logistic regression analysis was used to determine the strength of the relationship between risk variables and STH infections. Of the 243 participants (mean age: 8.99 ± 1.57 years), 12 (4.94%, 95% CI: 2.60%–8.50%) were infected with STH. The most common STH infection was hookworm (4.11%), followed by Trichuris trichiura (1.65%). More than 80% (n = 10, 83.33%) had a single intestinal parasite, while two (16.67%) were coinfected with two parasitic species. Infections were more prevalent among males (66.67%) compared to females (33.33%). Multiple regression analyses revealed that children above Grade 3 had a significantly higher prevalence of STH infections compared to those below Grade 3 (adjusted odds ratio [AOR] = 10.54; 95% CI: 1.24–89.14, p=0.031). Open defecation was also statistically associated with STH infections (AOR = 22.66; 95% CI: 1.18–433.58, p=0.038). This study highlights a low prevalence of STH infections in the study area, with hookworm being the most common. The potential risk factors identified were linked to educational level and open defecation practices. Improving sanitation and enhancing health education to raise public awareness about hygiene are essential strategies for controlling STH infections among primary schoolchildren in remote areas.